Pedagogical aspects of teaching programming in C# by means of creating a multi-module project - Yaschun, T.; Gromov, E. (Problems of Engineer-Pedagogical Education, 2018)
The profession of a programmer at the height of the development of the IT industry is one of the most demanded in the labor market. Working in an IT company helps to ensure social security and a decent standard of living. Many people would like to learn programming, but this process is complex and ambiguous. There are different approaches to teaching programming. The authors present a brief analytical review of existing methods and technologies for such training. It is concluded that there are a variety of similar approaches that differ both in the field of application (school, university, courses, etc.) and in orientation (from theoretical to practical). The analysis of existing approaches allowed the authors to suggest their own method of teaching programming, based on the use of a multi-module project. Each module of the project includes the solution of a separate task, starting from simple linear calculations and ending with the work with files and databases. At the same time, pedagogical principles of instruction are observed, such as the sequence of the course, the systematic nature of scientific knowledge, the gradual transition from simple to complex. However, each of the gradually more complicated tasks implies a solution not in a separate small project, but looks like an integral part of a large general project. Therefore, the development of such a project during laboratory studies allows students to learn the syntactic constructions of the programming language, to do practical programming activities, to develop skills in project activity and algorithmic thinking. In the future, the development of a software component of a multi-module project and an experimental study of the effectiveness of the method are suggested.